Structural, rheological and gelatinization properties of wheat starch granules separated from different noodle-making process. (January 2020) - Hong, Jing; An, Di; Li, Limin; Liu, Chong; Li, Mingfei; Buckow, Roman; Zheng, Xueling; Bian, Ke
Abstract: In this study, three typical wheat cultivars (ZM366, AK58, and ZM103) with high, medium, and low gluten strength, respectively, were selected as the raw material. The starch granules separated from different stages of the noodle-making process, including kneading, resting, sheeting, cutting, and drying, were used to explore the structure, dynamic rheology, and quality of the noodles. The D50 (median diameter) of the starch granules decreased during the noodle-making process, and the reduction was enhanced by an increase in the gluten strength of the flour. Between steps 4 and 5 of the noodle-making process, the solubility of ZM103 variety increased from 4.3% to 5.0% at 80 °C, while the peak viscosity decreased from 3626 to 3386 mPa s, which resulted in a decrease in the cooking loss of noodles. Similar trend was observed in the ZM366 and AK58 varieties. The gelatinization enthalpy was reduced, suggesting that the crystalline regions of the starch granules were destroyed during the kneading process. Between steps 4 and 5 of the noodle-making process, the elastic modulus of the starch granules significantly increased, while the temperature at which maximum elastic modulus was decreased, indicating an increase in the crystalline stability of starch during the drying process. Correlation analysis indicated that the changes occurred to the gelatinization property was primarily due to the change in the particle size. Graphical abstract: Image 1 Highlights: Peak viscosity of starch was decreased gradually during noodle-making process. The increased smaller starch granules would decrease its thermal stability. Higher damaged starch content was produced in kneading and cutting steps. Cooking loss of noodles was improved by the increased solubility in drying step. Elastic modulus of starches was increased obviously after drying step.